Cerebral cavernous malformation development in chronic mouse models driven by dual recombinases induced gene deletion in brain endothelial cells. Issue 12 (December 2022) - Yang, Xi; Dai, Zifeng; Gao, Caixia; Yin, Yongqiang; Shi, Changbin; Liu, Renjing; Zhuge, Qichuan; Huang, Yue; Zhou, Bin; Han, Zhiming; Zheng, Xiangjian
Cerebral cavernous malformation (CCM) is a brain vascular disease which can cause stroke, cerebral hemorrhage and neurological deficits in affected individuals. Loss-of-function mutations in three genes ( CCM1, CCM2 and CCM3 ) cause CCM disease. Multiple mouse models for CCM disease have been developed although each of them are associated with various limitations. Here, we employed the Dre-Cre dual recombinase system to specifically delete Ccm genes in brain endothelial cells. In this new series of CCM mouse models, robust CCM lesions now develop in the cerebrum. The survival curve and lesion burden analysis revealed that Ccm2 deletion causes modest CCM lesions with a median life expectance of ∼10 months and Ccm3 gene deletion leads to the most severe CCM lesions with median life expectance of ∼2 months. The extended lifespan of these mutant mice enables their utility in behavioral analyses of neurologic deficits in adult mice, and allow the development of methods to quantify lesion burden in mice over time and also permit longitudinal drug testing in live animals.